1994
DOI: 10.1037/0021-843x.103.3.505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anxiety on eating: Does palatability moderate distress-induced overeating in dieters?

Abstract: When confronted with an anxiety-producing threat to self-esteem, restrained eaters (dieters) increase their food consumption. The functional explanation suggests that increased eating temporarily counteracts or masks dysphoria for the restrained eater; externality or stimulus sensitivity theories propose that distress shifts the dieter's attention to external stimulus properties (e.g., taste) and to activities stimulated by such external cues. In an attempt to distinguish between these two explanations, anxiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0
7

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 22 publications
6
103
0
7
Order By: Relevance
“…Furthermore, this variable also related positively to BMI in the men in the normal weight group. These conclusions had already been obtained in previous studies 24 . Resorting to ingestion as a way of controlling emotional problems results in the person being caught up in a vicious circle from which it is then very difficult to escape.…”
Section: Eating Habits and Attitudes And Their Relationship With Bodysupporting
confidence: 77%
“…Furthermore, this variable also related positively to BMI in the men in the normal weight group. These conclusions had already been obtained in previous studies 24 . Resorting to ingestion as a way of controlling emotional problems results in the person being caught up in a vicious circle from which it is then very difficult to escape.…”
Section: Eating Habits and Attitudes And Their Relationship With Bodysupporting
confidence: 77%
“…In support, many experimental studies using the original Restraint Scale (RS; Herman, Polivy, Pliner, Threlkeld, & Munic, 1978) have found that restrained eaters show disinhibition of restraint under conditions of negative emotions, while non-restrained eaters decrease their eating or do not change their food intake (e.g., Polivy et al, 1994). However, the link between dietary restraint and overeating was not replicated in experimental studies in which the restraint scales of the Dutch Eating Behavior Questionnaire (DEBQ; Van Strien, Frijters, Bergers, & Defares, 1986) or the Three-Factor Eating Questionnaire (TFEQ; Stunkard & Messick, 1985) were used (e.g., Chua, Touyz, & Hill, 2004;Lowe & Maycock, 1988;Van Strien, & Ouwens, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, an increase in food intake in response to negative emotions-emotional eating-has been considered to be an 'inapt' response (Heatherton, Herman, & Polivy, 1991). Negative emotions have been shown to result in overeating in obese individuals (e.g., Van Strien & Ouwens, 2003), in eating-disordered women (e.g., Agras & Telch, 1998), and in normal-weight dieters (e.g., Polivy, Herman, & McFarlane, 1994). It is therefore suggested that the relation between eating and emotion is influenced, at least partly, by particular characteristics of an individual (Greeno & Wing, 1994;Schachter et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…The boundary model suggests two classes of variables that can impair the regulatio n of eating in restrained eaters and induce overeating, namely the experience of strong emotions, and a previous violation of the diet boundary. There has been some empirical support for both the emotion hypothesis (e.g., Baucom & Aiken, 1981;Frost, Goolk asian, Ely & Blanchard, 1982;Heatherton, Herman, & Polivy, 1991;Heatherton, Striepe & Wittenberg, 1998;Herman, Polivy, Lank & Heatherton, 1987;Polivy, Herman & McFarlane, 1994) and the assumption that dietary violations induce overeating (Herman & Mack, 1985;Herman, Polivy & Esses, 6 1987;Hibscher & Herman, 1977). However, there is also evidence that exposure to palatable food tempts restrained eaters into overeating (Fedoroff, Polivy & Herman, 1997;Jansen & van den Hout, 1991).…”
Section: Classic Theories Of the Regulation Of Eatingmentioning
confidence: 99%